Revealing the nuclearity of iron citrate complexes at biologically relevant conditions - Gracheva, Maria; Klencsár, Zoltán; Homonnay, Zoltán; Solti, Ádám; Péter, László; Machala, Libor; Novak, Petr; Kovács, Krisztina (Biometals, 2024)
Citric acid plays an ubiquitous role in the complexation of essential metals like iron and thus it has a key function making them biologically available. For this, iron(III) citrate complexes are considered among the most significant coordinated forms of ferric iron that take place in biochemical processes of all living organisms. Although these systems hold great biological relevance, their coordination chemistry has not been fully elucidated yet. The current study aimed to investigate the speciation of iron(III) citrate using Mössbauer and electron paramagnetic resonance spectroscopies. Our aim was to gain insights into the structure and nuclearity of the complexes depending on the pH and iron to citrate ratio. By applying the frozen solution technique, the results obtained directly reflect the iron speciation present in the aqueous solution. At 1:1 iron:citrate molar ratio, polynuclear species prevailed forming most probably a trinuclear structure. In the case of citrate excess, the coexistence of several monoiron species with different coordination environments was confirmed. The stability of the polynuclear complexes was checked in the presence of organic solvents.
Keywords: Iron; Citrate ligands; Iron metabolism; EPR; železo; železité sloučeniny; citráty; Ferric Compounds; Citric Acid; kyselina citronová; Mössbauer spectroscopy; Citrates